Capital Expenditure and Investment on Economic Growth in West Papua Province 2015-2019 - Kumba Digdowiseiso (Budapest International Research and Critics University, 2021)
This study was conducted to know the effect of capital expenditure and investment on economic growth in West Papua in 2015-2019. First, sampling was carried out using the saturated sampling technique with the number of samples obtained in 13 districts/cities. Panel data with Least Square Dummy Variable (SLDV) model estimation is used as an analysis method and Stata 16 functions as a data processing program. The research then found that the capital expenditure variable had a negative and insignificant effect on economic growth. Then it was found that the investment variable has a positive and significant impact on economic growth. Compared with the results of studies using only independent variables, the use of control variables (population and average length of schooling) will present the most significant coefficient of determination at the time of full regression. These results then indicate that the control variable has a strong influence on economic growth.